Salt impregnated desiccant matrices for ‘open’ thermochemical energy conversion and storage: improving energy density utilisation through hygrodynamic & thermodynamic reactor design - Casey, Sean P.; Aydin, Devrim; Elvins, Jon; Riffat, Saffa (Elsevier, 2017)
In this study, the performance of three nano-composite energy storage absorbents; Vermiculite-CaCl2 (SIM-3a), Vermiculite-CaCl2-LiNO3 (SIM-3f), and the desiccant Zeolite 13X were experimentally investigated for suitability to domestic scale thermal energy storage. A novel 3 kWh open thermochemical reactor consisting of new meshed tube air diffusers was built to experimentally examine performance. The results were compared to those obtained using a previously developed flatbed experimental reactor. SIM-3a has the best cyclic behaviour and thermal performance. It was found that 0.01 m3 of SIM-3a can provide an average temperature lift of room air, ΔT = 20 °C over 180 min whereas for SIM-3f, ΔT < 15 °C was achieved. Zeolite provided high sorption heat in close approximation with SIM-3a, however, the higher desorption temperature requirements coupled with poor cyclic ability remain as obstacles to the roll out this material commercially. The study results clearly show that the concept of using perforated tubes embedded inside the heat storage material significantly improves performance by enhancing the contact surface area between air → absorbent whilst increasing vapour diffusion. The results suggest a linear correlation between thermal performance and moisture uptake, ΔT–Δw. Determining these operating lines will prove useful for predicting achievable temperature lift and also for effective design and control of thermochemical heat storage systems.